2021
DOI: 10.21203/rs.3.rs-86575/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic analysis of the expression and prognosis relevance of FBXO family reveals the significance of FBXO1 in human breast cancer

Abstract: Background: Breast cancer (BC) remains a prevalent and common form of cancer with high heterogeneity. Making efforts to explore novel molecular biomarkers and serve as potential disease indicators, which is essential to effectively enhance the prognosis and individualized treatment of BC. FBXO proteins act as the core component of E3 ubiquitin ligase, which play essential regulators roles in multiple cellular processes. Recently, research has indicated that FBXOs also play significant roles in cancer developme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Depletion of FBXO16 results in increased levels of β-catenin, which in turn promotes cancer cell invasion, tumor growth and epithelial-mesenchymal transition (21). In breast cancer, FBXO16 is considered to be a potential clinical target and prognostic biomarker for patients with different molecular types of breast cancer (22). In addition, it has been reported that increasing the number of cytotoxic Tim-3 + /CD8 + T cells can promote effective anti-tumor immunity, and PTPN2 is an attractive tumor immunotherapy target in immune cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of FBXO16 results in increased levels of β-catenin, which in turn promotes cancer cell invasion, tumor growth and epithelial-mesenchymal transition (21). In breast cancer, FBXO16 is considered to be a potential clinical target and prognostic biomarker for patients with different molecular types of breast cancer (22). In addition, it has been reported that increasing the number of cytotoxic Tim-3 + /CD8 + T cells can promote effective anti-tumor immunity, and PTPN2 is an attractive tumor immunotherapy target in immune cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…SLC5A12 was an active source of lactate transmembrane transporter, which is mainly involved in sodium ion transport [50,51]. FBXO2 ,and MAD2L2 were involved in ubiquitination processes [52,53], which regulated the milk protein and fat metabolic mechanism [54]. DRAXIN was related to Akt, which could impact milk synthesis [55,56].…”
Section: Discussionmentioning
confidence: 99%